Scientific breeding of winter bread wheat in the Non-Сhernozem zone of Russia: the history, methods and results - B. I. Sandukhadze; R. Z. Mamedov; M. S. Krakhmalyova; V. V. Bugrova (Вавиловский журнал генетики и селекции)
The article describes the main stages and achievements of the breeding of winter bread wheat (Triticum aestivum L.) in the Non-Chernozem zone for more than a century. The beginning of breeding work was laid by D.L. Rudzinsky on the experimental field of the Moscow Agricultural Institute. Beginning from the 1940s, under the leadership of Academician N.V. Tsitsin, and then Prof. G.D. Lapchenko, the method of distinct hybridization with blue wheatgrass (Agropyron glaucum (Desf. ex DC.) Roem. & Schult.) was actively used. The resulting wheat-wheatgrass hybrids had an average winter hardiness, increased grain quality and productivity. Cultivar Zarya developed in the 1970s (by individual selection from the F3 cross combination of cv. Mironovskaya 808 × line 126/65 (in the pedigree of this line, there is a wheat-wheatgrass hybrid PPG 599)) had a high yield and was widely used in further crosses. In the 1980s, Academician B.I. Sandukhadze achieved a significant increase in yield by using the method of intermittent backcrosses due to the producing of varieties with a new morphoecotype (cvs Inna, Pamyati Fedina, etc.), namely, winter-hardy, short stemmed (dwarf), and productive. Cultivar Moskovskaya 39 (registration in 1999) was referred to strong wheat, with a stable protein content of 15–16 %, gluten 30–35 %. Produced in the 2000s, cvs Moskovskaya 56, Nemchinovskaya 57, Galina, Nemchinovskaya 24, Nemchinovskaya 17, and Moskovskaya 40 have a high adaptability to the environment of the region; give a high yield and quality of grain. The area of crops of these cultivars in Russia occupies more than 2 million ha. The current trends in wheat breeding are indicated, the production yield of commercial cultivars of breeding by the Federal Research Center “Nemchinovka”over 12.0 tons per ha and the protein content in the grain up to 17 % are shown. As a result of succession, originality and application of the methodology of scientific breeding, the yield of winter bread wheat in the period from the beginning of the last century to the present has increased from 1.0 to 12.0 and more tons per ha.